2013
DOI: 10.1093/ndt/gft070
|View full text |Cite
|
Sign up to set email alerts
|

Uraemic sarcopenia: aetiology and implications

Abstract: The term uraemic myopathy has been used loosely to describe the skeletal muscle abnormalities in uraemic patients. However, it does not fully explain the observed abnormalities as recent research has documented a normal skeletal muscle physiology in the presence of reduced muscle force, selective structural changes and significant muscle wasting. Ageing is associated with sarcopenia (muscle wasting) and an increase in the prevalence of chronic kidney disease (CKD), which accelerates the normal physiological mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
223
4
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(246 citation statements)
references
References 144 publications
3
223
4
16
Order By: Relevance
“…This prevalence is in line with a previous report in CKD stage$3 (16) and prevalent hemodialysis patients (17). It has been proposed that advanced CKD is a condition associated with a process of "accelerated aging" (11,12) and that the effect of various prevalent CKD-associated catabolic alterations may explain why sarcopenia is such a prominent typical feature in CKD (14). Although a lack of control group in our study does not allow us to make solid conclusions, the observed prevalence is within the range reported in geriatric populations (8)(9)(10).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This prevalence is in line with a previous report in CKD stage$3 (16) and prevalent hemodialysis patients (17). It has been proposed that advanced CKD is a condition associated with a process of "accelerated aging" (11,12) and that the effect of various prevalent CKD-associated catabolic alterations may explain why sarcopenia is such a prominent typical feature in CKD (14). Although a lack of control group in our study does not allow us to make solid conclusions, the observed prevalence is within the range reported in geriatric populations (8)(9)(10).…”
Section: Discussionsupporting
confidence: 91%
“…CKD is considered a risk factor for accelerated aging (11), and prospective studies in older adults with CKD have quantified the risk for physical disability and cognitive decline as being approximately double that of the age-matched general population (12). Although the term sarcopenia is often used in the literature to describe muscle derangements in patients with CKD (13)(14)(15), there are only two studies that have formally assessed its prevalence and clinical correlates. Sarcopenia was more prevalent in individuals with CKD stage$3 than in individuals with normal renal function (16), whereas it affected one third of prevalent hemodialysis patients (17).…”
Section: Introductionmentioning
confidence: 99%
“…Although originally known as a condition related to aging, various international societies currently recognize the important role of catabolic diseases, such as chronic kidney disease (CKD), in the etiology of sarcopenia [1][2][3][4]. In fact, metabolic derangements inherent to CKD lead to increased protein catabolism, resulting in diminished muscle mass and function, independently of age [14,15]. Therefore, it can be hypothesized that CKD patients are prone to develop sarcopenia.…”
mentioning
confidence: 99%
“…Chronic kidney disease is a catabolic state that activates different intracellular signaling pathways that decrease protein synthesis and increase protein degradation [23]. Some of the pathological mechanisms described in the literature that favor this catabolic state involve metabolic acidosis, increase angiotensin II, systemic inflammation and a sedentary lifestyle [24,25].…”
Section: Introductionmentioning
confidence: 99%